Differences in step characteristics and linear kinematics between rugby players and sprinters during initial sprint acceleration. Issue 10 (26th November 2018) - Wild, James J.; Bezodis, Ian N.; North, Jamie S.; Bezodis, Neil E.
Abstract: The initial steps of a sprint are important in team sports, such as rugby, where there is an inherent requirement to maximally accelerate over short distances. Current understanding of sprint acceleration technique is primarily based on data from track and field sprinters, although whether this information is transferable to athletes such as rugby players is unclear, due to differing ecological constraints. Sagittal plane video data were collected (240 Hz) and manually digitised to calculate the kinematics of professional rugby forwards ( n  = 15) and backs ( n  = 15), and sprinters ( n  = 18; 100 m personal best range = 9.96–11.33 s) during the first three steps of three maximal sprint accelerations. Using a between-group research design, differences between groups were determined using magnitude-based inferences, and within-group relationships between technique variables and initial sprint acceleration performance were established using correlation. Substantial between-group differences were observed in multiple variables. Only one variable, toe-off distance, differed between groups ( d  = −0.42 to −2.62) and also demonstrated meaningful relationships with sprint performance within all three groups ( r  = −0.44 to −0.58), whereby a stance foot position more posterior relative to the centre of mass at toe-off was associated with better sprint performance. While toe-off distance appears to be an important technical feature for sprint acceleration performance in both sprinters and rugby players, caution should be applied to the direct transfer of other kinematic information from sprinters to inform the technical development of acceleration in team sports athletes.